Behavioral Intervention in Children with Functional Abdominal Pain Disorders: A Promising Option - Saini, Shubhanshu; Narang, Manish; Srivastava, Shruti; Shah, Dheeraj (Turkish Journal of Gastroenterology, 2021)
Background: The objectives of this study were to identify and classify patients with functional abdominal pain disorders (FAPD) into its various subtypes as per the Rome IV criteria and to evaluate the underlying psychological factors and the effect of behavioral intervention in children with FAPD. Methods: A validated Questionnaire on Pediatric Gastrointestinal Symptoms (QPGS) based on Rome IV criteria was used to identify and classify children presenting with abdominal pain. The children diagnosed as having FAPD were referred for psychological screening to evaluate for underlying psychosocial problems. The scales namely Pediatric Anxiety Rating Scale (PARS), Depression self-rating scale (DSRS), and Visual Analog Scale (VAS) were administered to children to assess the response of the child to behavioral therapy. Results: Of 100 children, 32, 26, 22, and 20% of children belonged to the subtypes of functional abdominal pain—not otherwise specified, abdominal migraine, irritable bowel syndrome, and functional dyspepsia, respectively. The most common associated psychosocial factors were academic burden, poor financial condition, exam-related stress, and bullying at school. The influence of behavioral therapy was statistically significant (P < .05). The mean (±standard deviation) PARS and DSRS scores were significantly reduced at 3 months of follow-up. Discussion: The most common subtypes reported were functional abdominal pain—not otherwise specified and abdominal migraine. Psychological factors such as academic burden, poor financial condition, exam-related stress, and bullying at school need to be ruled out in children with this condition. Non-pharmacological intervention such as behavioral therapy can confer a remarkable improvement in the symptoms of children with FAPD.